THERMAL DECOMPOSITION OF WOOD FIBERS: THERMAL SIMULATION USING THE F-TEST STATISTICAL TOOL - Ornaghi, Heitor L.; Ornaghi, Felipe Gustavo; Neves, Roberta Motta; De Oliveira, Daniel Magalhaes [UNESP]; Poletto, Matheus (Editura Acad Romane, 2021)
Wood biomass is an alternative for fossil fuels to produce bioenergy, due to its low cost, renewability and environmental friendliness. In order to use biomass as an energy source, understanding its thermal degradation behavior is highly recommended. This work focuses on the thermal degradation of wood fibers belonging to different species (Pinus elliotti (PIE), Eucalyptus grandis (EUG) and Mezilaurus itauba (ITA)), commonly used by the Brazilian lumber industry. The prediction of their degradation kinetics and overall thermal behavior was performed based on the most common theoretical data using the F-test statistical tool. The most probable degradation mechanism was found to be autocatalytic for all the wood fibers tested, with three different degradation steps. The results obtained were in accordance with the findings recently reported in the literature using other fitting methods. It was found that cellulose is the major contributor to Arrhenius parameters, while hemicelluloses - to reaction order.
Keywords: modelling and simulation; wood fiber; thermal decomposition; pyrolysis; model-fitting